PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KARYAWAN PT HONORIS INDUSTRY - Ismartaya, Ismartaya; Kartini, Tini; Rahmanissa, Nurul Febrianti (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to test the direct effect of workload and compensation on turnover intention through job satisfaction with 100 workers from PT Honoris Industry as the sample. Study findings revealed that workload has a direct, negative, and significant effect on job satisfaction, and compensation has a positive and significant effect directly on job satisfaction. Workload has a positive and significant direct effect on turnover intention and compensation has a negative and significant effect directly on turnover intention. Job satisfaction can mediate the indirect influence of workload on employee turnover intentions and job satisfaction can mediate the indirect positive and significant influence of compensation on turnover intention. Keywords: Workload; Compensation; Turnover Intention; Job Satisfaction